VIABILITAS INOKULAN DALAM BAHAN PEMBAWA GAMBUT, KOMPOS, ARANG BATOK DAN ZEOLIT YANG DISTERIL DENGAN IRADIASI SINAR GAMMA Co-60 DAN MESIN BERKAS ELEKTRON - Sindy Marieta Putri; Iswandi Anas; Fahrizal Hazra; Ania Citraresmini (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2010)
Carrier is one of the important factor to determine the quality of biofertilizer. The inoculant carriers should contain no or less microbial contaminant. The purpose of this research was to investigate viability of Azospirillum, Azotobacter and Phosphate Solubilizing Fungi inoculants in carrier material that were sterilized by Gamma Irradiation Co-60 and Electron Beam Machine (EBM). Each inoculants was injected to the sterilized peat, compost, coconut shell charcoal and zeolite. Viability of inoculants in steriled carrier was evaluated at 0, 7, 14, 42 and 70 days after preparation. The stirage was done in incubator at 25ºC. The result of viability of Azospirillum, Azotobacter and Phosphate Solubilizing Fungi inoculants on sterilized carrier material by Gamma Irradiation Co-60, EBM and autoclave tended to decline during storage 70 days at room temperature (250C). Viability of Azospirillum inoculants in zeolite sterilized by Gamma Irradiation Co-60 and autoclave gave the highest numbres of viable cells. Storage of these inoculants at 25ºC for 70 days only reduce the number of viable cells by 11.1%. Viability of Phosphate Solubilizing Fungi inoculants in coconut shell charcoal or compost sterilized by Gamma Irradiation Co-60 went down by 99.8% after 70 days. The sterilization of carriers by using autoclave or Gamma Irradiation Co-60 were better than EBM sterilization. . Keywords: Carrier, Electron Beam Machine, Gamma Irradiation Co-60, sterilization, viability